Engaging and Retaining Students in Online Learning - Ali Abusalem; Lorraine Bennett; Dimitra Antonelou-Abusalem (Athens Institute for Education and Research, 2024)
Before the COVID-19 outbreak, universities were already exploring the potential of online education. Colleges and universities throughout the world became more reliant on online learning management systems (LMSs) and videoconferencing tools like 'Zoom' and 'Microsoft Teams' during the 2020-2021 campus' lockdowns. The transition from traditional face-to-face teaching to online learning presented significant difficulties for universities, particularly those that depended heavily on international students. The project reported in this paper was undertaken in Australia in 2021 at the request of a private higher education institution. A new student-centric version of the Moodle learning management system (LMS) was created to maximise the platform's pedagogical, communicative, and informational capabilities. The purpose of this article is to demonstrate how online learning platforms that are flexible, utilise embedded interactive features and resources, and are freely available can enhance and support the delivery of quality online education. The paper discusses how well-designed learning management systems have the capacity to motivate, engage and retain students in online learning. Academics, at both the undergraduate and graduate levels, as well as those working in curriculum development and information technology at institutions of higher learning, may find this article to be of interest and value.